Characterization of Mechanical Properties of Epoxy Reinforced with Glass Fiber and Coconut Fiber. (2019) - Marimuthu, K. Prakash; Kumar, S. Mohan; Kumar, V. Ravi; Govindaraju, H.K.
Abstract: The present work deals with the characterisation polymer matrix composites combining glass fiber and fiber got from coconut. The composite was prepared using hand layup process and sufficient precaution has been taken to ensure there is homogeneity. The composite is composed of 60% epoxy resin, 10% glass fiber and 30% coconut fiber. Various mechanical tests like micro hardness test, tensile strength, impact strength test has been carried out to characterise the composite. The various mechanical properties like density, micro hardness and tensile strength are affected when the coconut fibers were added. The impact strength and flexural strength of the composite increases while ultimate tensile strength decreases. The study has come up with prospective results and further research has to be done to examine the effect of fiber content, fiber orientation, loading pattern etc. Studies on corrosive wear and other tribological properties can reveal newer things, which can enable us to use the composite that is combination of epoxy and coconut fibers in newer and newer applications.